Hubungan Rasio Lingkar Pinggang Pinggul dan Komposisi Tubuh dengan Hipertensi pada Lansia di Unit Pelaksanaan Teknis Daerah Griya Werdha Jambangan Surabaya - Li’izza Maret Frisqiyaturrohmah (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Elderly will experience changes in body composition which will affect the Waist to Hip Ratio (WHR) and have an impact on blood pressure. Hypertension is often found in the elderly in Indonesia. The aim of this study was to determine the relationship and differences in WHR and body composition between hypertensive and non-hypertensive elderly. The design used in this research is case control. The population of this study included all elderly people in the Griya Werdha Jambangan Surabaya Regional Technical Implementation Unit (RTIU) with a total sample of 76 elderly people consisting of 38 hypertensive and 38 non-hypertensive. The results of the research were the relationship between getting WHR, fat mass, muscle mass (p = 0,000), bone mass (p = 0,026), and fluid mass (p = 0,049). The results of the study were differences in WHR, fat mass, muscle mass, bone mass (p = 0,000), and fluid mass (p = 0,001). The odds ratio (OR) value shows that elderly people with obesity WHR have a risk of 27,4, more fat mass and muscle mass below normal have a risk of 24,4, bone mass below normal has a risk of 5,8, and less fluid mass has a risk of 5,1 times developing hypertension. Based on these results, it can be concluded that there is a relationship between WHR and body composition and hypertension, and there are differences in WHR ​​and body composition values between hypertensive and non-hypertensive elderly.